2017
DOI: 10.18632/oncotarget.17839
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum tartrate-resistant acid phosphatase isoform 5a levels in metabolic syndrome

Abstract: BackgroundTartrate-resistant phosphatase isoform 5a is expressed in tumor-associated macrophages and is a biomarker of chronic inflammation. Herein, we correlated serum tartrate-resistant phosphatase isoform 5a levels with metabolic syndrome status and made comparisons with traditional markers of inflammation, including c-reactive protein and interleukin-6.MethodsOne hundred healthy volunteers were randomly selected, and cut-off points for metabolic syndrome related inflammatory biomarkers were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The observed delta values in serum TRAP 5a, between baseline and 12 weeks and TRAP 5a/5b ratio at week 1, were correlated to changes in serum insulin indicating that TRAP 5a is involved in metabolic changes, which is in conjunction with previous reports [33,36]. However, the exact mechanism by which TRAP 5a responds to metabolic changes and insulin sensitivity/resistance remains to be elucidated.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The observed delta values in serum TRAP 5a, between baseline and 12 weeks and TRAP 5a/5b ratio at week 1, were correlated to changes in serum insulin indicating that TRAP 5a is involved in metabolic changes, which is in conjunction with previous reports [33,36]. However, the exact mechanism by which TRAP 5a responds to metabolic changes and insulin sensitivity/resistance remains to be elucidated.…”
Section: Discussionsupporting
confidence: 64%
“…The TRAP 5a/TRAP 5b ratio was also significantly altered with approximately a 4-fold increase). The abundance of TRAP 5a, that is, 4-fold more than TRAP 5b, has previously been reported in healthy individuals where TRAP 5a has been in the range of 4-8 ng/ml [33,34], while other studies have reported TRAP 5b levels in the range of 1-3 ng/ml [23,24]. Thus far, there are no studies that have investigated the ratio between TRAP 5a and 5b directly in the same serum sample from humans.…”
Section: Discussionmentioning
confidence: 92%